2020
DOI: 10.1016/j.bbrc.2019.09.104
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SRF protein stability by an autophagy-dependent pathway

Abstract: Serum response factor (SRF), a key transcription factor, plays an important role in regulating cell functions such as proliferation and differentiation. Most proteins are unstable, and protein stability is regulated through the ubiquitin-proteasome system (UPS) or the autophagy lysosome pathway (ALP). Whether SRF is degraded and what mechanisms control SRF protein stability remain unexplored. Western blot analyses of cells treated with cycloheximide (CHX), a protein synthesis inhibitor, showed that SRF was deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with our observation that SRF is largely expressed in myofibroblast nuclei in our cell and mouse models. Another study demonstrated that SRF is degraded via autophagy rather than the ubiquitin-proteasome pathway [ 36 ]. Our experiments support this, having shown that SRF was degraded by ezetimibe-activated autophagy and accumulated during autophagy inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our observation that SRF is largely expressed in myofibroblast nuclei in our cell and mouse models. Another study demonstrated that SRF is degraded via autophagy rather than the ubiquitin-proteasome pathway [ 36 ]. Our experiments support this, having shown that SRF was degraded by ezetimibe-activated autophagy and accumulated during autophagy inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, this also implies that other TFs such as CREB- ( 57 ) or SRF-directed IEGs known to regulate autophagy ( 58 , 59 ) might provide a link between neuronal activity and autophagy gene regulation. So far, only 2 instances of an SRF connection with autophagy have been reported ( 60 , 61 ). Here, SRF protected MNs from rotenone-induced cellular death and reduced synuclein aggregation; however, this beneficial effect was abolished by either Beclin1 or Atg5 knockdown, implying that autophagy induction is a critical component of the neuroprotective SRF effects ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…This cell culture finding supports our conclusion that, in response to neuronal activity, SRF modulates autophagy to convey neuroprotection. Finally, SRF was shown to be subject to autophagy-dependent degradation ( 61 ). This points at a reciprocal regulatory mechanism whereby SRF might regulate mRNA abundance of autophagy-encoding genes.…”
Section: Discussionmentioning
confidence: 99%
“…RefSeq (NCBI Reference Sequence Database) was used to obtain the reference genomes of the bacteria. The assembled contigs were then loaded with their respective reference genomes into Medusa (http://combo.dbe.unifi.it/medusa (accessed on 20 July 2023)) [21] to determine the orientation and the order among the contigs to produce longer scaffolds [22,23]. The genome sequence data was uploaded to the Type Strain Genome Server (TYGS), a free bioinformatics platform available at https://tygs.dsmz.de (accessed on 26 July 2023), for full genome-based taxonomic analysis [24] and, for the determination of closely related type strains, a pairwise comparison of genomic sequences, phylogenetic inferences, and grouping of species and subspecies based on the type [24].…”
Section: Bacterial Identificationmentioning
confidence: 99%